The Integration of Cognitive Behavioral Therapy and Islamic Counseling in Addressing Academic Burnout among University Students in Yogyakarta: An Islamic Reframing Case Study: Integrasi Cognitive Behavioral Therapy dan Konseling Islam dalam Menangani Academic Burnout Mahasiswa di Kampus Yogyakarta: Studi Kasus Reframing Islami - Nurjannah; Abdul Malik Al Karim Malik (Institut Agama Islam Negeri Parepare, 2026)
ABSTRACT This study examines academic burnout among Muslim university students and explores the recovery process through Islamic counseling based on Islamic Reframing. Previous studies have largely discussed burnout from psychological, cognitive, and social perspectives, while the spiritual dimension remains underexplored in Muslim student contexts. Using a qualitative case study design, this research focused on one Muslim student, identified as ZF, who experienced emotional exhaustion, declining learning motivation, and negative self-perceptions. Data were collected through in-depth interviews during individual counseling sessions, clinical observation, and counseling documentation. The data were analyzed reflectively by tracing changes in cognitive, emotional, behavioral, and spiritual dimensions. The findings show that Islamic Reframing works as a cognitive-spiritual recovery mechanism. By integrating cognitive restructuring with Islamic values such as niyyah, ikhtiar, tawakkal, sabr, and amanah, the counselee reinterpreted academic pressure not as personal failure but as part of a meaningful learning process. The study contributes to Islamic Guidance and Counseling by offering an operational model that integrates CBT and Islamic counseling for addressing academic burnout.